2019
DOI: 10.1590/2236-8906-91/2018
|View full text |Cite
|
Sign up to set email alerts
|

Croton (Euphorbiaceae) in the State of São Paulo, Brazil: an update

Abstract: Croton (Euphorbiaceae) in the State of São Paulo, Brazil: an update). An updated key for Croton species in the State of São Paulo is presented as well as new occurrences of the genus and the reestablishment of Croton thermarum Müll. Arg. For those species of Croton that were not included in previous studies in the State of São Paulo, we provided: the original publication, synonymy, global geographic distribution, vegetation type, and a representative herbarium collection. This study increases the number of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…However, our results indicate that they also frequent floral structures of varied architectures. Examples include inflorescences with small, numerous flowers (as seen in Forsteronia, Schefflera, and Pera) (Larrosa & Duarte 2006;Gagliardi et al 2018), thyrsoid inflorescences (as in Croton) (Caruzo et al 2019), and brush-type inflorescences (such as those found in Eucalyptus and Eriotheca) (Stevens 2001;Moré et al 2014). While brush-type inflorescences have been previously reported as food resources for hawkmoths (Darrault & Schlindwein 2002;Avila et al 2010), our study marks the first instance of inflorescences with small flowers being noted as potential food resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our results indicate that they also frequent floral structures of varied architectures. Examples include inflorescences with small, numerous flowers (as seen in Forsteronia, Schefflera, and Pera) (Larrosa & Duarte 2006;Gagliardi et al 2018), thyrsoid inflorescences (as in Croton) (Caruzo et al 2019), and brush-type inflorescences (such as those found in Eucalyptus and Eriotheca) (Stevens 2001;Moré et al 2014). While brush-type inflorescences have been previously reported as food resources for hawkmoths (Darrault & Schlindwein 2002;Avila et al 2010), our study marks the first instance of inflorescences with small flowers being noted as potential food resources.…”
Section: Discussionmentioning
confidence: 99%
“…2018), thyrsoid inflorescences (as in Croton ) (Caruzo et al. 2019), and brush‐type inflorescences (such as those found in Eucalyptus and Eriotheca ) (Stevens 2001; Moré et al. 2014).…”
Section: Discussionmentioning
confidence: 99%
“…America, South America, Asia, and North Africa (Barrera et al, 2016). Its biodiversity consists of about 300 genera and 7500 species (Rahman et al, 2013) All parts of the plant, including leaves, stems, and roots, are used as traditional remedies to treat and manage various ailments (Caruzo et al, 2019;Seebaluck et al, 2015). Different researchers have described the presence of multiple phytoconstituents with biological properties, including antimicrobial and anticarcinogenic (Prado, 2017;Beltrán Villanueva et al, 2013).…”
Section: Geographic Distribution Of the Euphorbiaceae And Moraceae Fa...mentioning
confidence: 99%
“…The nonpolar fraction and its subfractions of S. Grantus and E. umbellate stem exhibited a cytostatic effect on human tumor cell lines (glioma, breast, kidney, and lung), inhibited by 0.37 to 2.9 μg/mL, with the compound 3,4,12,13-tetraacetylphorbol-20-phenylacetate with antiproliferative activity against glioma (25.2 μg/mL), kidney (24.1 μg/mL), lung (31.1 μg/mL) and leukemia (65.3 μg/mL) cell lines (Campos et al, 2016). Croton macrobothrys Baill is a tree from southern Brazil popularly known as "dragon's blood" (Caruzo et al, 2019). The n-hexane, dichloromethane, and methanol extracts of the leaf have in vitro antiproliferative activity against kidney (786-0), colon (HT-29) leukemia (K562), ovarian (NCI-ADR/RES), lung (NCI-H460), mammary (MCF-7), prostate (PC-3), ovarian (OVCAR-3), glioma (U251) and melanoma (UACC-62) cell lines.…”
Section: Anticancer and Antiproliferative Agentsmentioning
confidence: 99%
See 1 more Smart Citation